2005
DOI: 10.1002/ajh.20515
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mycophenolate mofetil as single‐agent therapy for refractory immune thrombocytopenic purpura

Abstract: Refractory disease occurs in 25% or more of adults with idiopathic (immune) thrombocytopenic purpura (ITP). Therapy to elevate the platelet count may be required in a proportion of these patients. Immunosuppressive agents such as prednisone, azathioprine, cyclophosphamide, and cyclosporin have been shown to be effective treatments in a proportion of patients with refractory ITP. A newer immunosuppressive medication, mycophenolate mofetil (MMF), has been used successfully with acceptable toxicity in solid organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 36 publications
1
45
0
5
Order By: Relevance
“…Our findings contrast with several reports or clinical studies showing prolonged response with such therapies, but patients showed less refractory disease than our patients. [13][14][15][16][17][18][19] Despite the efficacy of HSCT, the high risk of mortality associated with this procedure (1 death in our cohort) argues for its proposal for patients with no alternative therapeutic option only. However, the combination of Tpo-RAs with immunosuppressant drugs was effective with an overall response rate (R 1 CR) of 70% in the 10 patients who received this treatment.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings contrast with several reports or clinical studies showing prolonged response with such therapies, but patients showed less refractory disease than our patients. [13][14][15][16][17][18][19] Despite the efficacy of HSCT, the high risk of mortality associated with this procedure (1 death in our cohort) argues for its proposal for patients with no alternative therapeutic option only. However, the combination of Tpo-RAs with immunosuppressant drugs was effective with an overall response rate (R 1 CR) of 70% in the 10 patients who received this treatment.…”
Section: Discussionmentioning
confidence: 83%
“…[76][77][78][79][80][81][82] We begin MMF at a dose of 500 mg orally twice per day and increase the dose to 1000 to 1500 mg twice per day after 2 weeks. Protocols that use this approach have demonstrated overall response rates of 50% to 60%.…”
Section: Tiermentioning
confidence: 99%
“…Protocols that use this approach have demonstrated overall response rates of 50% to 60%. [76][77][78][79][80][81] Durability of response after discontinuation of therapy is variable. 77,79,82 MMF is generally well tolerated; principal adverse effects include headache and gastrointestinal symptoms.…”
Section: Tiermentioning
confidence: 99%
“…About 40% of splenectomized patients either do not respond or relapse after surgery [6], approximately 10% of patients have early perioperative or delayed infections, and some develop surgical complications, although rarely fatal. In case of relapse or resistant to corticosteroids ITP, other immunosuppressive drugs can be used including azathioprine, cyclosporine A, cyclophosphamide, danazol, mycophenolate mofetil, all with marginal efficacy [7][8][9][10][11]. Intravenous immunoglobulin (IVIG) and anti-D are also used in the treatment of ITP, especially when rapid improvement of platelet count is needed (in case of life-threatening bleeding or prior to splenectomy or other surgical procedures).…”
Section: Open    Accessmentioning
confidence: 99%